2018
DOI: 10.1007/s00404-018-4725-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of poor responders following growth hormone co-treatment with IVF/ICSI mild stimulation protocol: a retrospective cohort study

Abstract: The results suggested that the adjuvant GH treatment in mild stimulation protocol for poor responders could significantly improve good-quality embryo rate, and might therefore improve the clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
1
20
1
Order By: Relevance
“…While this is not a direct measurement of embryo quality, it does imply that those with GH may have more opportunities for ET (and ensuing pregnancies) in later cycles. Nonetheless, several other reports have demonstrated that GH enhanced embryo quality as assessed by morphological grading [5,16], although in our study this enhancement was not detectable. It is possible that such embryos (and the oocytes from which they were derived) have higher competency for generating pregnancies, which is not measured by current morphological grading systems.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…While this is not a direct measurement of embryo quality, it does imply that those with GH may have more opportunities for ET (and ensuing pregnancies) in later cycles. Nonetheless, several other reports have demonstrated that GH enhanced embryo quality as assessed by morphological grading [5,16], although in our study this enhancement was not detectable. It is possible that such embryos (and the oocytes from which they were derived) have higher competency for generating pregnancies, which is not measured by current morphological grading systems.…”
Section: Discussioncontrasting
confidence: 95%
“…In accordance with this previous work on fresh transfers [12,13], the current findings indicated that the use of GH as an adjuvant cotreatment during IVF stimulation had a positive outcome on fresh ET and in addition, in subsequent FET cycles. As GH was not administered during the FET cycles, this suggested that the potential beneficial effects of GH may extend to embryo quality as presented previously [5,9,16], rather than involving an effect on endometrium receptivity [15,17]. However, in our previous studies on embryos generated under GH action, we failed to demonstrate that the adjuvant altered embryo quality to a measurable extent, as the proportion of highquality embryos on morphological assessment was the same with or without GH [12,13].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…GH has been applied in the treatment of infertility, especially for poor responders. Some studies showed that GH administration during ovarian stimulation can improve IVF/ICSI outcomes, such as oocyte quality, pregnancy rate, and live birth [12][13][14]. In 2010, a Cochrane review suggested that due to few number of RCTs and small sample size, the role of GH in IVF/ICSI needs further research [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the double ovarian stimulation, that is the ovarian stimulation in follicular and luteal phases within a single ovarian cycle, seems capable of increasing the number of retrieved oocytes and available embryos for the single patient (64). The first data have been published on possible advantages of a GH co-treatment with the mild stimulation protocol or the GnRH antagonist protocol in poor responders (6567). Some RCTs and meta-analysis have also been published regarding LH supplementation within the rFSH stimulation in IVF cycles: there is no agreement on the benefit of this therapy in the general population, while particularly in POR patients it showed an improvement of the clinical pregnancy rate and live birth rate (51, 52, 68, 69).…”
Section: Ovarian Response Prediction and Managementmentioning
confidence: 99%